The Influence of Taxpayer Knowledge, Motor Vehicle Tax Socialization, Taxpayer Awareness, and Motor Vehicle Tax Amnesty Program on Motor Vehicle Taxpayer Compliance - Panggita Mauli Hidayat; Ardan Gani Asalam (Smart Society, 2025)
Motor vehicle tax is a key source of regional revenue, yet taxpayer compliance often remains low due to limited knowledge, weak socialization, low awareness, and the varied impact of tax amnesty programs. This study aims to analyze the influence of taxpayer knowledge, motor vehicle tax socialization, taxpayer awareness, and the motor vehicle tax amnesty program on motor vehicle taxpayer compliance at the Samsat Office of Subang Regency in 2024. A quantitative approach and descriptive method were employed, using questionnaires distributed to 104 respondents selected through incidental sampling. The data were analyzed using validity and reliability tests, multiple linear regression, t-test, and F-test. The results indicate that taxpayer knowledge, motor vehicle tax socialization, taxpayer awareness, and the motor vehicle tax amnesty program simultaneously have a significant effect on motor vehicle taxpayer compliance. Partially, taxpayer knowledge has a highly significant effect on taxpayer compliance, while motor vehicle tax socialization, taxpayer awareness, and the tax amnesty program do not have a significant effect on motor vehicle taxpayer compliance in the Subang Regency Samsat Office in 2024. This study implies that increasing knowledge about vehicle taxes should be prioritized as an effort to improve compliance and policy in Subang Regency, rather than simply using tax amnesty programs or socialization.